Gestão de custos em uma clínica popular multiprofissional de serviços de saúde: uma abordagem para a implementação de um sistema de custo - Gomes, Cristiano Freitas (2014)
It is known that the complexities of large hospital sectors require large amount of resources for their implementation and operation, and the equipment end up having relatively short lifespan and spending are too high for the characteristic of the patients treated, unlike outpatient specialties where the cost is returned to skilled labor. Currently, health services have sought to control your spending. Every day the modern environment has been shown in favor of change and competitiveness not only for quality but at a lower cost has been considered. Propose a system of cost management for health clinics popular services that assists managers can have a better competitive position in the negotiations. The objective this study was to analyze the process of management of costs by absorption costing, in popular multi-professional clinical health services. This research is the research-action type. The data had been collected through primary documents and analyzed by documentary and descriptive analysis. The absorption costing takes care of requirements of Management of Costs National Program (PNGC). This is a easy method to standardize the costs information units that were managed.